Growth of anaerobic methane-oxidizing archaea and sulfate reducing bacteria in a high pressure membrane-capsule bioreactor - Timmers, Peer H. A. (2015)
Communities of anaerobic methane-oxidizing archaea (ANME) and sulfate-reducing bacteria (SRB) grow slowly, which limits the ability to perform physiological studies. High methane partial pressure was previously successfully applied to stimulate growth, but it is not clear how different ANME subtypes and associated SRB are affected by it. Here, we report on the growth of ANME-SRB in a membrane capsule bioreactor inoculated with Eckernförde Bay sediment that combines high-pressure incubation (10.1 MPa methane) and thorough mixing (100 rpm) with complete cell retention by a 0.2-m-pore-size membrane. The results were compared to previously obtained data from an ambient-pressure (0.101 MPa methane) bioreactor inoculated with the same sediment. The rates of oxidation of labeled methane were not higher at 10.1 MPa, likely because measurements were done at ambient pressure. The subtype ANME-2a/b was abundant in both reactors, but subtype ANME-2c was enriched only at 10.1 MPa. SRB at 10.1 MPa mainly belonged to the SEEP-SRB2 and Eel-1 groups and the Desulfuromonadales and not to the typically found SEEP-SRB1 group. The increase of ANME-2a/b occurred in parallel with the increase of SEEP-SRB2, which was previously found to be associated only with ANME-2c. Our results imply that the syntrophic association is flexible and that methane pressure and sulfide concentration influence the growth of different ANME-SRB consortia. We also studied the effect of elevated methane pressure on methane production and oxidation by a mixture of methanogenic and sulfate-reducing sludge. Here, methane oxidation rates decreased and were not coupled to sulfide production, indicating trace methane oxidation during net methanogenesis and not anaerobic methane oxidation, even at a high methane partial pressure.